2006
DOI: 10.3892/ijo.28.6.1385
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect and condition of pegylated interferon α with paclitaxel on glioblastoma

Abstract: Glioblastomas are highly vascularized tumors and anti-angiogenic strategy is one of the most promising therapeutic approaches to treat brain tumors. Interferon • (IFN-•) as a single agent or combined with standard chemotherapy has been shown to inhibit various tumors, but the effect of combination anti-angiogenic therapy on brain tumors has not been well studied. We determined the optimal dose and schedule of pegylated IFN-• (PEG-IFN-•) against U-87MG human glioblastoma cells growing orthotopically in nude mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Our combination therapy showed the anti-angiogenic potential by down regulating expression of VEGF and EGFR in glioblastoma cells. A previous study reported synergistic efficacy of combination of pegylatedinterferon-alpha (PEG-IFN-a) and TX in glioblastoma U87MG cells due to inhibition of proliferation and angiogenesis [31]. Similarly, a Phase II clinical trial of TX and topotecan with filgrastim (also known as G-CSF) showed therapeutic effects in glioblastoma patients [32], indicating importance of TX in the combination therapy to control growth of glioblastoma.…”
Section: Discussionmentioning
confidence: 96%
“…Our combination therapy showed the anti-angiogenic potential by down regulating expression of VEGF and EGFR in glioblastoma cells. A previous study reported synergistic efficacy of combination of pegylatedinterferon-alpha (PEG-IFN-a) and TX in glioblastoma U87MG cells due to inhibition of proliferation and angiogenesis [31]. Similarly, a Phase II clinical trial of TX and topotecan with filgrastim (also known as G-CSF) showed therapeutic effects in glioblastoma patients [32], indicating importance of TX in the combination therapy to control growth of glioblastoma.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently chemotherapy seems essential in the treatment of GBM. A widely used chemotherapeutic drug, paclitaxel, has been proven effective in the treatment of GBM [3][4][5][6][7], acting by promoting the assembly and stabilization of microtubules inhibiting cellular division [8], preventing de-polymerization of the assembled microtubules and thereby halts mitosis or cell division and binding to Bcl-2 which normally blocks the process of apoptosis, allowing apoptosis to proceed [9,10]. However, its high hydrophobicity seriously restricts the practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Production of type I IFNs, in particular IFN-b and members of the IFN-a subfamily, is essential for adequate viral clearance and initiation of an adaptive immune response in mammals [1][2][3]. Type I IFNs are used as approved therapeutics for various viral and neurologic diseases, such as hepatitis C virus infection and multiple sclerosis, as well as solid and hematologic cancers, including melanoma, glioblastoma, and various types of leukemia [4][5][6][7][8]. Their growth inhibitory, anti-angiogenic, and immunomodulatory effects likely contribute to the antitumor activity of type I IFNs in the clinical setting and in preventing virus spread in vivo.…”
Section: Introductionmentioning
confidence: 99%